2002
DOI: 10.1039/b206616p
|View full text |Cite
|
Sign up to set email alerts
|

Flow analysis–hydride generation–Fourier transform infrared spectrometry. A new analytical technique for the simultaneous determination of antimony, arsenic and tin

Abstract: The combination of flow analysis (FA), hydride generation (HG) and Fourier transform infrared (FTIR) spectrometry is proposed as a novel and powerful analytical technique for the individual and simultaneous determination of antimony, arsenic and tin in aqueous samples. The analytes were transformed into the volatile hydride form by on-line reaction with sodium tetrahydroborate in acidic medium. The gaseous analyte hydrides [M(n)H(m), (g)] generated, were transported by means of a carrier gas stream inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other multi-analyte HG procedures featuring As that have already been discussed are by Bings et al, 257 Li et al, 236 Matsumoto et al, 237,238 Abranko et al, 258 and Gallignani et al 259 There are relatively few HG-AES procedures reported in this review period. Apart from the work of Matsumoto et al (see above) the only other report is by Guchardi and Hauser, 246 who were able to detect As and Sb, via HG, as well as Hg by CV generation, in their capacitively coupled microplasma sustained in a fused silica capillary of 250 mm id.…”
Section: Chemical Vapour Generationmentioning
confidence: 89%
See 1 more Smart Citation
“…Other multi-analyte HG procedures featuring As that have already been discussed are by Bings et al, 257 Li et al, 236 Matsumoto et al, 237,238 Abranko et al, 258 and Gallignani et al 259 There are relatively few HG-AES procedures reported in this review period. Apart from the work of Matsumoto et al (see above) the only other report is by Guchardi and Hauser, 246 who were able to detect As and Sb, via HG, as well as Hg by CV generation, in their capacitively coupled microplasma sustained in a fused silica capillary of 250 mm id.…”
Section: Chemical Vapour Generationmentioning
confidence: 89%
“…Three procedures in which Sb was determined alongside As have already been discussed: Sun et al, 253 Cava-Montesinos et al 251,252 Other reports of multi-element determinations that include Sb are those by Bings et al, 257 Matsumoto et al, 237,238 Abranko 258 and Gallignani. 259 Guchardi and Hauser 246 were able to detect Sb along with As, via HG, as well as Hg, by CV generation, in their capacitatively coupled microplasma sustained in a fused silica capillary of 250 mm id. Wlodarczyk and Zyrnicki 296 investigated the spectroscopic characteristics of a low power argon MIP sustained in a resonant TE 101 rectangular cavity on introduction of gaseous species, including SbH 3 , produced from ethanol-water solutions by continuous HG.…”
Section: Chemical Vapour Generationmentioning
confidence: 99%
“…Applications that can be found in the literature typically deal with a small number of compounds in gas mixtures. [31][32][33][34][35] Due to the broad spectral features that result from the larger Doppler broadening, the confusion limit is reached sooner for more complex mixtures. In these cases, hyphenated techniques like GC/FTIR are often used to obtain higher specificity.…”
Section: The Rotational Fingerprint In Analytical Applicationsmentioning
confidence: 99%
“…It is well established that the carrier gas flow rate significantly affects the analytical signal in both hydride generation [23][24][25] and gaseous FTIR spectrometric systems. 26 This parameter was studied in the range of 2 -20 mL min -1 .…”
Section: Influence Of Carrier Gas Flowmentioning
confidence: 99%